Is the Saudi public aware of Middle East respiratory syndrome? - Omar A. Al-Mohrej; Sarah D. Al-Shirian; Salman K. Al-Otaibi; Hani M. Tamim; Emad M. Masuadi; Hana M. Fakhoury (Elsevier, 2016)
Summary: To limit the spread of Middle East respiratory syndrome coronavirus (MERS-CoV) in Saudi Arabia, the Ministry of Health tried to raise public awareness using different public campaigns. We aimed to measure public awareness of MERS in Saudi Arabia.A cross-sectional study was conducted between May and June 2014 using a newly designed Arabic questionnaire that was distributed and completed online.We analyzed the response of 1149 respondents across Saudi Arabia. We found that 97% of the participants were aware of MERS. In addition, 72% realized that coughing and sneezing could spread the infection. Furthermore, 83% thought that some patients with MERS could be cured. Moreover, 62% knew that no vaccine can prevent the disease. However, only 36% realized that taking antibiotics will not stop the infection, and only 41% recognized that no medication has yet been manufactured to treat it. Regarding protection measures, 74% used hand sanitizers, 43% avoided crowded places, and 11% wore masks in public places. Moreover, only 47% knew that bats and camels are the primary source of the virus. As anticipated, this level of awareness varied between the different categories of the studied population. Female, married, older, and more educated participants were significantly more knowledgeable about the disease.Public awareness of MERS is generally sufficient. However, some false beliefs about treatment were fairly common. In addition, almost half of the population remains unaware that bats and camels are the most likely sources of the virus. Keywords: Coronavirus, MERS, Public awareness, Saudi Arabia